A combination of monoacylglycerol crystalline network and hydrophilic antioxidants synergistically enhances the oxidative stability of gelled algae oil. Issue 1 (21st December 2018) - Wang, Qiang; Decker, Eric Andrew; Rao, Jiajia; Chen, Bingcan
Abstract : In this study, base algae oil was gelled through the formation of a crystal network using food-grade monoacylglycerol (MAG). Abstract : In this study, base algae oil was gelled through the formation of a crystal network using food-grade monoacylglycerol (MAG). The impact of the MAG concentration (5, 10, 20 wt%) and water content (0, 5 wt%) on the physical properties and oxidative stability of the gelled algae oil was systematically investigated. The antioxidative activity of 300 μM hydrophilic antioxidant, i.e., ascorbic acid and green tea extract, on the oxidative stability of the gelled algae oil by 20 wt% of MAG was also examined. The results obtained clearly showed that the melting temperature, melting of entropy, and complex modulus of the algae oil increased with increasing the MAG concentration. The addition of 5 wt% water could negatively affect the strength of the MAG crystal network, while a physically stable gel system could only be formed with 20 wt% MAG. The stronger crystal network formed by 20 wt% MAG retarded the lipid oxidation of algae oil due to the creation of a physical barrier to restrain the attack from oxygen. The addition of green tea extract could further synergize with the MAG crystalline network by forming a thermodynamic barrier to effectively quench the radicals, thus prolonging the oxidative stability of algae oil 4-fold longer than that of the base algae oil.